Парторги военной поры - Рощин Иван Илларионович (Политиздат, 1990)
Экземпляры: Ф. 3 (20210329) / Инвентарный номер: 27433 / Цена: 00.70 / Сис.шифр: 63.3(2)722.4 / Авт.знак: Р81 / ГРНТИ: 03 / ББК: 63.3(2)722.4